Alih Fungsi Lahan Pertanian Menjadi Tempat Permukiman di Kelurahan Jati Hilir Kecamatan Pariaman Tengah Kota Pariaman - Nopriadi, Diki; Dasrizal, Dasrizal; Zuriyani, Elvi (Pendidikan Geografi, 2013)
This research aim to to get information, analysing and studying data about displacing agriculture farm function become setlement place in kelurahan Jati Hilir Kecamatan Pariaman Tengah Kota Pariaman. Research type the used is descriptive of korelasional. Research population is one who personate family head (KK). In Kelurahan Jati Hilir Kota Pariaman Tengah which amount to 348 KK. Research Sampel in this research is taken with technique of random sampling with proportion equal to 30% so that sampel amount to 55 KK. Pursuant to analysis of regresi linear modestly is, double ( correlation and multiple) hence can be taken by the following conclusion: ( 1) there are influence of growth of resident to displacing agriculture farm function become setlement place in kelurahan Jati Hilir Kecamatan Pariaman Tengah Kota Pariaman because thitung > ttabel ( 4,279 > 1,673) with strength is ( r = 0,507) and small contribution ( 25,7%), ( 2) there are influence of aksesibilitas to displacing agriculture farm function become setlement place in kelurahan Jati Hilir Kecamatan Pariaman Tengah Kota Pariaman because thitung > ttabel ( 2,407 > 1,670) with low strength ( r = 0,314) and contribution very small ( 9,9%), ( 3) there are influence of land price to displacing agriculture farm function become setlement place in kelurahan Jati Hilir Kecamatan Pariaman Tengah Kota Pariaman because thitung > ttabel ( 1,834 > 1,670) with low strength ( r = 0,244) and contribution very small ( 6,0%) and ( 4) there are influence of growth of resident, land price and aksesibilitas by together to displacing agriculture farm function become setlement place in kelurahan Jati Hilir Kecamatan Pariaman Tengah Kota Pariaman because Fhitung > F of[is tables of ( 11,350 > 3,150) with strength of strength ( r = 0,633) and small contribution ( 40,0%).